Influence of slope on subtalar pronation in submaximal running performance - de Oliveira, Vinicius Machado (Brazilian Society of Orthopedics and Traumatology, 2013)
OBJECTIVE: : To investigate the slope influence on the maximal subtalar pronation in submaximal running speeds. METHODS: : Sixteen endurance runners participated of a running economy (RE) test in a treadmill with different slopes (+1%, +5%, +10%, +15%). For each slope a 4-minute run was performed with no rest break for the purpose of measuring the magnitude of kinematic variables by means of a high frequency video camera positioned in a frontal-posterior plane of the individual. RESULTS: : No significant differences were verified in maximal subtalar pronation between legs and between the slopes adopted, showing that changes of running technique due to modifications of slope aren't enough to modify the behavior of maximum subtalar pronation. CONCLUSION: : The subtalar pronation is independent of slope, which may be influenced by other intervening variables. Level of Evidence II, Diagnostic Study